Theoretical AB initio calculation of entropy and heat capacity of dialkylsulfones in the gas phase - A. S. Mkhitaryan; Z. K. Papanyan; L. S. Gabrielyan; S. A. Markarian (ՀՀ ԳԱԱ հրատ.)
The present study describes the theoretical ab initio calculation of entropy, heat capacity and internal energy for a series of dialkylsulfones (dimethyl-, ethylmethyl-, diethyl sulfones). The thermodynamic properties of dialkylsulfones have been calculated by combining quantum mechanics with statistical thermodynamics by using Gaussian 09 software package. Geometry optimizations of isolated sulfone’s molecules are performed by the restricted Hartree-Fock (RHF) and the density functional theory (DFT/B3PW91) methods with 6-311++G(d,p) extended basis set. The approximations of the methodology are those of the rigid-rotor/harmonic oscillator formalism. Because theoretically calculated entropy, heat capacity and heat content are sensitive to vibrational frequencies, the appropriate scaling factor has been used to recalculate harmonic vibration modes. Իրականացվել է դիալկիլսուլֆոնների (դիմեթիլ-, էթիլմեթիլ-, դիէթիլսուլֆոնների) էնտրոպիայի, ջերմունակության և ներքին էներգիայի տեսական քվանտաքիմիական հաշվարկը: Դիալկիլսուլֆոնների նշված թերմոդինամիկական հատկությունները հաշվարկվել են քվանտային մեխանիկայի և վիճակագրական թերմոդինամիկայի համակցումով Gaussian 09 ծրագրային փաթեթի օգնությամբ: Մեկուսացված մոլեկուլների երկրաչափության օպտիմիզացիան իրականացվել է Հարթրի-Ֆոկի սահմանափակ (RHF) և խտության ֆունկցիոնալի տեսության (DFT/B3PW91) մեթոդներով` 6-311++G(d,p) ընդլայնված բազիսային հավաքածուով: Կիրառվել է կոշտ ռոտոր/հարմոնիկ օսցիլյատորի մոտավորությունները: Քանի որ տեսականորեն հաշվարկված էնտրոպիայի և ջերմունակության արժեքները զգայուն են տատանողական հաճախությունների նկատմամբ, օգտագործվել է համապատասխան մասշտաբային գործակիցը` վերահաշվարկելու հարմոնիկ հաճախությունները: Проведен теоретический квантово-химический расчет энтропии, теплоемкости и внутренней энергии диалкилсульфонов (диметил-, этилметил-, диэтилсульфоны). Термодинамические свойства диалкил-сульфонов были рассчитаны путем комбинирования квантовой механики со статистической термодинамикой с использованием программного пакета Gaussian 09. Оптимизация геометрии изолированных молекул сульфонов проводилась ограниченным методом Хартри-Фока (RHF) и методами теории функционала плотности (DFT/B3PW91) с расширенным базисным набором 6-311++G(d,p). Методология расчета основана на формализме жесткого ротора/гармонического осциллятора. Так как теоретически рассчитанные энтропия и теплоемкость чувствительны к колебательным частотам, соответствующий коэффициент масштабирования использовался для перерасчета гармонических колебаний.
Keywords: Science; Chemistry; Physical Chemistry